Are All Dictators Equal? The Selective Targeting of Democratic Sanctions against Authoritarian Regimes - Christian von Soest; Michael Wahman (German Institute of Global and Area Studies (GIGA), 2013)
Since the end of the Cold War, Western powers have frequently used sanctions as a reaction to declining levels of democracy and human rights violations in authoritarian regimes. However, some of the world's most repressive authoritarian regimes have never been subjected to sanctions, while other more competitive autocracies have been exposed to repeated sanction episodes instigated by Western democracies as an attempt to enhance democracy and human rights. In this paper, we investigate how the United States and the European Union have selectively used sanctions as a tool to improve the level of democracy in targeted authoritarian states. Using a new dataset on democratic sanctions between 1990 and 2010, time-series-cross-sectional logistic regression and a number of strategically selected case studies, we find strong support for the suggestion that senders select economically and politically vulnerable targets where the expected probability of sanction success is high.
Keywords: 300; democratic sanctions; authoritarian regimes; democratization; imposition; threats; Autoritäres System; Demokratisierung; Sanktion; EU-Staaten